Analisis Kelayakan Investasi Pada Bangunan Puskesmas Halong Dengan Metode Net Present Value - K M B Sahureka; F A Sangadji; I Oppier; S I Latuconsina (Jurnal MESIL (Mesin Elektro Sipil), 2024)
The construction of the new Halong Puskesmas was carried out because the old puskesmas no longer met the standards set by the government. The construction of the new Halong health center is intended so that in the future the people in Halong village and the surrounding area can get good service. Consistent building maintenance is a requirement that must be met, especially for buildings that are to be used commercially. Life Cycle Cost is used to find the value and percentage of the initial cost, replacement and maintenance costs and operational costs during the economic life of the building from the data provided by the Halong Health Center. The Net Present Value is used to analyze the feasibility of the investment by finding the present value of the difference between income and expenses during the economic life of the Halong Health Center. From the results, it is found that the four components that make up the Life Cycle Cost are the initial cost of Rp. 5,534,999,131.79, Operational Costs of Rp. 1,082,976,586.66, maintenance and replacement costs of Rp. 15,226,565,089.41. The final NPV calculation is -2,693,330,679.61. NPV<0.